Until they have faces: the ethics of facial allograft transplantation - Agich, G (BMJ Group, 2005)
The ethical discussion of facial allograft transplantation (FAT) for severe facial deformity, popularly known as facial transplantation, has been one sided and sensationalistic. It is based on film and fiction rather than science and clinical experience. Based on our experience in developing the first IRB approved protocol for FAT, we critically discuss the problems with this discussion, which overlooks the plight of individuals with severe facial deformities. We discuss why FAT for facial deformity is ethically and surgically justified despite its negative portrayal in the media.